PREPARATION OF TEACHING MATERIALS FOR ACCOUNTING PRACTICUM GRADE XII (1ST SEMESTER) AT SMK NEGERI 1 TANJUNGPINANG - Santi Yopie; Evi Yessy Angery (Universitas Internasional Batam, 2022)
School is a place to get knowledge and knowledge from the subject matter given by the teacher. The pandemic that lasts for a long time has forced all people to practice social distancing. One of the areas that has been significantly affected is education because the teaching and learning process must be carried out online. Distance learning (online) can reduce productivity in the teaching and learning process due to limited facilities and available media. The purpose of this program is to support the completeness of materials or facilities in teaching so that it can be maximized. The methods that help the learning process, namely: modules, practice questions, powerpoints, and video explanations. The prepared teaching materials help school teachers in delivering material so that students can also better understand and understand the lessons to be conveyed by the school even though they are far away but can still maximize the learning process. As for other facilities or media, such as: online quizzes by using kahoot or the like so that they can be used as input for further service.